Evaluating the Compliance of Shopee Paylater and Shopee Paypinjam with Islamic Finance Principles: Ethical Challenges and Opportunities in Fintech - Rasulong, Ismail; Yuniarti, Andi; Rachman, Mutmainna; Rini (Li Falah: Journal of Islamic Economics and Business, 2024)
This study evaluates the compliance of Shopee Paylater and Shopee Paypinjam with Islamic finance principles by examining their operational mechanism. The research focuses on the challenges posed by interest rates, late fees, and transparency, which hindre adherence to Sharia ethics. A qualitative approach, including case studies and semi-structured interviews with users, was employed, supported by secondary data analysis. The findings reveal significant reveal significant non-compliance with Islamic finance principles, particularly due to the imposition of interest and late payment penalties, both considered forms of riba. Moreover, unclear repayment terms and hidden fees undermine the transparency and fairmenss central to Islamic finance practices. While the fintech services provide convenience and accessibility, they fail to meet the understanding of fintech in Islamic markets, highlighting the need for profit-sharing models, improved transparency, and Sharia-compliant regulatory frameworks. The findings offer practical insights for fintech providers, policymakers, and Sharia boards, emphasizing the importance of fostering trust and inclusivity in digital financial ecosystem. Future research should explore comparative analyses across different regions and incorporate the perspectives of various stakeholders.